Applications of foamed lightweight concrete - Mohd Sari, Kamarul Aini; Mohammed Sani, Rahim (EDP Sciences, 2017)
Application of foamed concrete is increasing at present due to high demand on foamed concrete structures with good mechanical and physical properties. This paper discusses on the use of basic raw materials, their characteristics, production process, and their application in foamed lightweight concrete with densities between 300 kg/m3 and 1800 kg/m3. It also discusses the factors that influence the strengths and weaknesses of foamed concrete based on studies that were conducted previously